2005
DOI: 10.1021/jm040899l
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Activity of Non-Platinum Xanthate Complexes

Abstract: To establish structure-activity relationships, derivatives of bis(O-alkyldithiocarbonato)platinum(II) complexes were analyzed. Eighteen bis(O-alkyldithiocarbonato) metal complexes were synthesized, and their cytotoxic activity on two human cancer cell lines was compared with the corresponding platinum bis(O-alkyldithiocarbonato) complexes and cisplatin. Complexes were synthesized with palladium, gold, nickel, copper, rhodium, and bismuth. Palladium and bismuth complexes were found to display significant cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…In this field, other studies [55] indicated that xanthate complexes of several metals, including gold, palladium and bismuth, are endowed with a high antitumor activity. It has also to be considered that xanthate ligands are reported to be, in general, less toxic than dithiocarbamate ligands [11].…”
Section: Apoptosis and Cell Cycle Studiesmentioning
confidence: 99%
“…In this field, other studies [55] indicated that xanthate complexes of several metals, including gold, palladium and bismuth, are endowed with a high antitumor activity. It has also to be considered that xanthate ligands are reported to be, in general, less toxic than dithiocarbamate ligands [11].…”
Section: Apoptosis and Cell Cycle Studiesmentioning
confidence: 99%
“…By contrast, the R ¼ cyclohexyl derivative was significantly less cytotoxic against MCF 7 (mammary carcinoma), which is relatively non responsive to cisplatin (I), than the compounds with smaller R groups. Interestingly, when cytotoxicity was scored at pH ¼ 6.8, mimicking the pH of a solid tumour, the potency was greater for the R ¼ Et and i-Pr compounds [77]. It was determined that the comparable binary platinum(II) xanthates were significantly more cytotoxic than the bismuth compounds which have potency comparable to cisplatin (I).…”
Section: Bismuth Compoundsmentioning
confidence: 99%
“…The anticancer potential of the complexes was evaluated in two human cancer cell lines which were either highly sensitive (MOLT-4) [17] or poorly sensitive (MCF-7) [18][19][20] to cisplatin. For comparison purposes, the in vitro cytotoxicity of these compounds against Chang Liver cell line was also studied.…”
Section: Cytotoxic Assaymentioning
confidence: 99%
“…Results are expressed in terms of IC 50 values, i.e., the concentration of drug required to inhibit cell growth by 50%. Results are summarized in Table 4, together with the reference standard cisplatin [17,18].…”
Section: Biological Activitymentioning
confidence: 99%